How Schools and Districts Meet Rigorous Standards Through Authentic Intellectual Work : Lessons From the Field. - King, M. Bruce (SAGE Publications, 2016)
Meet challenging standards by promoting students' authentic intellectual work There is no such thing as a simple formula for school improvement, but the Authentic Intellectual Work (AIW) framework presented in this book will help school- and district-based teams improve the quality of instruction, assessment, and curriculum for more rigorous and more equitable student learning. This book provides: Richly detailed case studies of successful AIW implementation at the statewide, districtwide, and individual school levels Illustrations of collaborative teaming to advance higher-order thinking, d.